FORMATION AND ACTIVITIES OF PROSECUTOR’S OFFICES IN INDEPENDENT UZBEKISTAN - Keldibekov, Yovqochti (Oriental Journal of History, Politics and Law, 2026)
This article examines the development of the prosecutor's office in independent Uzbekistan. It examines the emergence of prosecutorial bodies and their place in the public administration system. Based on this, it explores the legal foundations of the prosecutor's office's activities during the period of independence, in particular, changes in its powers and objectives enshrined in the Constitution and special laws, and summarizes development trends.